SOSIALISASI DAN EDUKASI TENTANG PERAN JAMU DALAM MENINGKATKAN SISTEM IMUNITAS TUBUH DALAM MENGHADAPI MUSIM PANCAROBA DI DESA SRIKUNCORO BENGKULU TENGAH - Dewi, Devi Cynthia; Rozi, Veby Fransisca; Novitasari, Deltari; Novega, Novega; Fitriza, Miki Kurnia; Miranda, Tenike Gita (Jurnal Pengabdian Masyarakat (Jupemas), 2024)
ABSTRACTThere are many ways to stay healthy and strengthen your immune system during this pandemic, immunity can't be built in a day, but the good news is that a balanced diet and drink and being physically and mentally active is usually enough to keep your immune system in good health. Herbal medicine may be an option to strengthen a person's immune system. Jamu is a traditional Indonesian herbal medicine that has been practiced for centuries in Indonesian society to maintain health and treat disease. Even though there are many modern medicines, herbal medicine is still very popular in rural and urban areas (Elfahmi et al., 2020). The aim of this service is to explain and educate about the role of herbal medicine in improving the body's immune system in facing the transition season in Srikuncoro Village, Central Bengkulu. The methods used were in the form of distributing leaflets, counseling through training about the role of herbal medicine to improve the immune system, as well as counseling and training for 50 people, and the service instrument in the form of distributing questionnaires and measuring with a pre-test to measure the participants' initial knowledge. The target of this community service is the entire community in Srikuncoro Village, Central Bengkulu. The results of the frequency data show that before counseling the results were in the good category of 88.46% for 39 respondents, the medium category for 11.54% for 10 respondents and the poor category for 3.85% for 1 respondent. It was concluded that the pre-test results were 88.46% in the good category with 1 respondent in the poor category and 10 respondents in the medium category. The post-test results were 98.2% with 50 respondents in the good category. And there is a significant influence between knowledge before and after the counseling is 0.02. It is hoped that this counseling and training can be applied by PKK mothers to make and consume traditional concoctions to increase endurance both in the family and in the surrounding environment. Keywords:  The Role of Herbal Medicine; Immune System; Transition Season